Pengaruh Harga, Promosi dan Kualitas Pelayanan Terhadap Loyalitas Pelanggan - Resha Arrigo Rivaldi; Sudarmadi (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The purpose of this study is to determine the relationship between price variables, promotions and service quality to AC Mulya Jaya customer loyalty. The approach in this study uses a quantitative method. The sampling technique in this study uses probability sampling and random sampling. In this study, a sample of 50 consumers who use service services or who buy air conditioners at the Mulya Jaya AC Store is used. According to the findings, there is a strong and substantial relationship between pricing, promotion, and customer loyalty. The third finding is that service quality also has a positive and significant influence on customer loyalty